Training for Hydrographic Surveyors at the Centre for Hydrographic Studies, Universiti Teknologi Malaysia - Sharif, Ayob (Fakulti Ukur dan Harta Tanah, 1995)
The Centre for Hydrographic Studies (CHS) established at the Faculty of Surveying and Real Estate, Universiti Teknologi Malaysia, is the only academic institution in the country presently focusing its effort toward the development of hydrographic surveying. One of the main objectives of the centre is to provide an education and training for hydrographic surveyors to cater for the increasing need of the country. This paper presents an overview of the establishment of the centre. However, the focus of this paper is to discuss on the design and development of the Hydrographic Surveying I (HYDRO I) course offered by the CHS to the hydrographic surveying community in Malaysia and the region.